Characteristics and Identification of the Metabolite Profile of Arabica Coffee Oil by Using the Gas Chromatography-Mass Spectrometry (GC-MS) - Purwasih, Rita; Alamsyah, Oke Junjunan; Mukminah, Nurul; Fathurohman, Ferdi (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
Indonesia is a tropical country that is suitable for coffee cultivation, and each coffee producing region has its own unique and distinct taste characteristics. This study aimed to determine the characteristics and identification of the metabolite profile of arabica coffee oil. The material used is coffee beans obtained from severals coffee Micro, Small, and Medium Enterprises (MSMEs) in Bukanagara Hamlet, Cupunagara Village, Cisalak, Subang-West Java. Coffee beans were roasted until medium to dark roast level. Coffee oil was extract from the ground coffee using n-hexane. Parameters to be observed included yield, specific gravity, acid number, peroxide number and identification of metabolite profiles by Gas Chromatography-Mass Spectrometry (GC-MS). The results of the study showed that arabica coffee oil had a yield of 9.43%, specific gravity of 0.94, an acid number of 0.78 mg NaOH/g and a peroxide number of 8.23 meq/kg. There was total 20 metabolite compounds identified in arabica coffee oil and based on the area of their distribution there are 11 compounds exist in high proportion. Keywords: Arabica coffee, Bukanagara, characteristics, GC-MS, metabolite profile.